F2. CHANGE IN PROLACTIN AND SEXUAL SIDE EFFECTS IN PATIENTS WITH SCHIZOPHRENIA WHO SWITCHED FROM PALIPERIDONE PALMITATE OR RISPERIDONE LONG-ACTING INJECTION TO ARIPIPRAZOLE LAUROXIL. (9th April 2019) - Kelly, Deanna; Claxton, Amy; Bidollari, Ilda; Du, Yangchun
Abstract: Background: Hyperprolactinemia is a common side effect of many antipsychotic medications, with the highest rates found with risperidone and paliperidone. Hyperprolactinemia may be asymptomatic or may be associated with adverse effects, such as irregular menses, gynecomastia, osteoporosis, infertility, and sexual dysfunction. These side effects may lead to decreased quality of life, as well as nonadherence to medication. Although hyperprolactinemia is a common side effect of paliperidone palmitate (PP) and risperidone long-acting injection (RLAI), little is understood about how a switch to a different long-acting injectable (LAI) antipsychotic may impact prolactin and related side effects. The current analysis examined change in serum prolactin and patient-reported sexual side effects in patients who switched from PP or RLAI to aripiprazole lauroxil (AL) as part of a 6-month, open-label, Phase 4 LAI switch study. Methods: This was a post hoc analysis of an open-label, 6-month prospective study of a transition to AL in patients with schizophrenia who were inadequately treated with PP or RLAI. Serum prolactin was measured at screening, baseline, month 1, month 2, month 3, and month 6 (or early termination). Sexual side effects were elicited by patient self-report using the subscale for sexual function from the UKU Side Effect Rating Scale at screening and at month 6 (or early termination). Results: At screening, all 37 males and 12 of 14 female patients (total = 96%) taking PP (n=50) or RLAI (n=1) exhibited elevated serum prolactin. At baseline, 36 males and 10 females continued to have elevated prolactin (total = 90%). For males, mean prolactin level was 29.54 ng/mL at screening and 29.33 ng/mL at baseline (normal range = 2.63–13.13 ng/mL). For females, it was 52.83 ng/mL at screening and 56.83 ng/mL at baseline (normal range = 2.74–26.72 ng/mL). Over the course of the study, serum prolactin levels declined for every patient and normalized in 94%. A completer analysis found that, after 6 months of treatment with AL, mean prolactin level declined from baseline by 22.96 ng/mL for males (n=23) and by 48.17 ng/mL for females (n=10). Only 2 of 33 patients (6%; both males) continued to have elevated serum prolactin levels after 6 months of AL treatment. On average, it took 2 months (2 injections of AL) for serum prolactin levels to normalize for both women and men. At screening, 82% of the patients reported experiencing sexual dysfunction in at least one domain; after 6 months of treatment with AL, the number of patients reporting any sexual dysfunction was reduced to 58%. At screening, the most frequent sexual symptom was "diminished sexual desire, " reported by 48% of the patients (50% of males and 44% of females). After 6 months of treatment with AL, the percentage of patients who continued to report diminished sexual desire was reduced to 18% overall (13% of males and 33% of females). Reports of ejaculatory dysfunction, premature ejaculation, and menstrual dysfunction also declined. No change was noted in female orgasmic dysfunction. Only one patient, whose prolactin levels were high at screening, discontinued due to gynecomastia. Discussion: In this post hoc analysis from a prospective, 6-month open-label study in patients with schizophrenia taking PP or RLAI (n=51), almost all patients had hyperprolactinemia when screened for participation (96%). Switching to AL resulted in a normalization of serum prolactin levels in 94% of the patients sampled (n=33) at 6 months. On average, mean prolactin level normalization occurred within 2 months of AL initiation. Overall, self-reported sexual side effects improved following the switch; the greatest improvement was noted in the domain of sexual interest.